DGI-025 Development of a Protocol For the Treatment of Vitamin D Deficiency/Insufficiency in Adults. (12th March 2013) - Kieran, M; O'Sullivan, D; Brady, J; McQuaid, S; Meegan, C
Abstract : Background: Recent medical research has highlighted that vitamin D deficiency/insufficiency is a significant public health problem. A UK study found that more than 50% of the adult population had insufficiency and 16% had deficiency. [1] Low vitamin D levels have been linked to rickets, malignancies, cardiovascular disease, type 2 diabetes and some autoimmune diseases. [1] Therefore, appropriate management of Vitamin D deficiency/insufficiency is essential. This increased awareness among prescribers of treating vitamin D deficiency was apparent in the Mater Misericordiae University Hospital (MMUH): Medicines Information enquiries regarding treatment of vitamin D deficiency had increased. Biochemistry assay numbers for vitamin D (25-hydroxy-vitamin D) had increased. Requests to the endocrinology service for guidance on the treatment of vitamin D deficiency had increased. MMUH clinicians were experiencing difficulty treating patients with vitamin D deficiency/insufficiency as: There were no definitive guidelines for the treatment of vitamin D deficiency/insufficiency. There is no licenced preparation containing cholecalciferol or ergocalciferol as a single drug formulation in Ireland. Guidance for MMUH clinicians was therefore necessary. Purpose: To develop a protocol for the treatment of vitamin D deficiency/insufficiency. Materials and Methods: Review of treatment algorithms for treatment of vitamin D deficiency/insufficiency in the literature. Compilation of vitamin D products currently available in Ireland. Liaison with MMUH clinical staff to ensure production of a protocol that is applicable to all disciplines. Results: A treatment algorithm was prepared detailing two specific guidelines for the treatment of: Vitamin D deficiency (serum 25-hydroxy-vitamin D <25 nmol/L) Vitamin D insufficiency (serum 25-hydroxy-vitamin D 25–50 nmol/L) The protocol recommends vitamin D preparations, including one unlicensed preparation, which are available in the MMUH and accessible in the community. The protocol also recognises the limitation of giving guidance on treating a condition that may be affected by numerous clinical scenarios or that may require input from specialist physicians. Where applicable, consultation with the relevant medical team(s) is recommended. Conclusions: MMUH patients diagnosed with vitamin D deficiency/insufficiency are treated in a standardised manner in accordance with available clinical evidence. The protocol ensures delays in treatment are minimised and physicians are aware of the particular considerations involved in the management of vitamin D deficiency/insufficiency. No conflict of interest.